Handbook of Drug Monitoring Methods Therapeutics and Drugs of Abuse - Dasgupta, Amitava (Humana Press : Imprint: Humana, 2008)
In Handbook of Drug Monitoring Methods: Therapeutics and Drug Abuse, authors discuss the different analytical techniques used in today's practice of therapeutic drug monitoring and drugs of abuse as well as alcohol testing with relevant theory, mechanism, and in-depth scientific discussion on each topic. This volume is the perfect handbook and quick reference for any clinical laboratory, allowing clinicians to find the potential source of a false-positive or a false-negative result in the daily operation of a toxicology laboratory. At the same time, this book can also be used as a reference for medical technologists, supervisors, laboratory directors, clinical chemists, toxicologists, and pathologists to find in-depth cause of a potential interference and what tests can be ordered to circumvent such problem. The volume's first half focuses on various issues of therapeutic drug monitoring. Additional chapters cover analysis of heavy metals, alcohol testing, and issues of drugs of abuse testing. These chapters are written by experts in their relative sub-specialties and also by the editor. Comprehensive and timely, Handbook of Drug Monitoring Methods: Therapeutics and Drug Abuse is the ideal text for clinicians and researchers monitoring alcohol and drug testing and other important tasks of toxicological laboratory services.